Answer:
h(4)=17
Step-by-step explanation:
h(g(x)), h(x)= 2x+9; g(x)=4
2(4)+9= 8+9=17
Answer:
k=10
Step-by-step explanation:
4k + 12= 52
minus 12 on both sides
4k=40
now divide by 4
k=10
Answer:
The awnser is D hope this helps :)
Step-by-step explanation:
This is called the Pythagorean theorem : a ² + b ² = c ². You can substitute any of the variable with any of the known numbers and then you all you have to do is isolate the variable. I hope that helps!!
Good morning
Answer:
NO
Step-by-step explanation:
Here we just substitute x and y by their values and see if the inequality still true or not
y = 3
6x + 3 = 6(2) + 3 = 15
since 3 < 15 then the inequality y > 6x + 3 is wrong.
______________________________________
:)